Multi-timescale morphological modelling of a dune-fronted sandy beach - Karunarathna, Harshinie; Brown, Jennifer; Chatzirodou, Antonia; Dissanayake, Pushpa; Wisse, Paul (My University, 2018)
Medium/long term trends (annual to decadal scale) of beach change are mostly used to make coastal management decisions. However, short term, extreme episodic events (short term) can erode the beach to exceed sustainable erosion thresholds thereby impacting long term trends of coastal change. Therefore, understanding coastal change at short and medium-long term (years to decades) timescales is essential to provide sustainable solutions to beach erosion. In this paper, we investigate and simulate the change of a beach-dune system for a megatidal coastline in the UK at storm timescale and at medium-long term timescale corresponding to sea level rise, in order to assess their significance in terms of beach management. The field site of choice is the Sefton coast, located in Liverpool Bay, United Kingdom. The approach used here involves process based modelling to determine storm-induced beach erosion and the application of modified Bruun Rule (Dean and Houston, 2016) to determine medium-long term evolution associated with climate change impacts. The application of the process-based model, XBeach, reveals that storm-induced short term beach erosion can be in the same scale or may surpass average medium/long term erosion thresholds and therefore, should be taken in to account when managing coastlines. Despite the complexities of the megatidal Sefton coast, the modified Bruun Rule proved to be capable of capturing long term beach profile change and assures that it can be confidently used to determine medium-long term beach-dune change due to sea level rise, once reliable estimates of longshore transport and sediment sources/sinks are made.
Keywords: 570